Изучение морфологических изменений поверхности эмали постоянных зубов in vitro под воздействием современных средств экзогенной профилактики кариеса = Investigation of morphological changes of permanent teeth enamel surface in vitro influenced by modern me - Khomenko, Larisa; Sorochenko, Grigoriy (Journal of Education, Health and Sport, 2015)
Khomenko Larisa, Sorochenko Grigoriy. Изучение морфологических изменений поверхности эмали постоянных зубов in vitro под воздействием современных средств экзогенной профилактики кариеса = Investigation of morphological changes of permanent teeth enamel surface in vitro influenced by modern means for exogenous caries prevention. Journal of Education, Health and Sport. 2015;5(6):384-394. ISSN 2391-8306. DOI 10.5281/zenodo.18809 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A384-394 https://pbn.nauka.gov.pl/works/568425 http://dx.doi.org/10.5281/zenodo.18809 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 20.06.2015. УДК 616.314.13 -091:616.314-002-084 ИЗУЧЕНИЕ МОРФОЛОГИЧЕСКИХ ИЗМЕНЕНИЙ ПОВЕРХНОСТИ ЭМАЛИ ПОСТОЯННЫХ ЗУБОВ IN VITRO ПОД ВОЗДЕЙСТВИЕМ СОВРЕМЕННЫХ СРЕДСТВ ЭКЗОГЕННОЙ ПРОФИЛАКТИКИ КАРИЕСА Л. А. Хоменко, Г. В. Сороченко Национальный медицинский Университет имени А. А. Богомольца, Киев, Украина (03680, г. Киев, ул. Зоологическая,1.) Кафедра детской терапевтической стоматологии и профилактики стоматологических заболеваний (Зав. кафедры – д. мед. н., проф. Хоменко Л.А.) Е-mail - sorochenkogw@mail.ru INVESTIGATION OF MORPHOLOGICAL CHANGES OF PERMANENT TEETH ENAMEL SURFACE IN VITRO INFLUENCED BY MODERN MEANS FOR EXOGENOUS CARIES PREVENTION L. Khomenko, G. Sorochenko Bogomolets National Medical University, Kyiv, Ukraine, (1, Zoologichna str., Kyiv, 03680) The department of pediatric and preventative dentistry (Head of the department of pediatric and preventative dentistry - M.D. in dentistry, professor L. Khomenko) Е-mail - sorochenkogw@mail.ru Хоменко Лариса Александровна д. мед. н., профессор, заведующий кафедры детской терапевтической стоматологии и профилактики стоматологических заболеваний Национального медицинского университета имени А. А. Богомольца. Адрес: г. Киев 03680, ул. Зоологическая, 1, тел.(факс) +380444831703 Е-mail : nmu.dts@gmail.com Larisa Khomenko M.D. in dentistry, Professor Head of the department of pediatric and preventative dentistry Bogomolets national medical university 1, Zoologichna str., Kyiv, 03680, tel.(fax) +380444831703 Сороченко Григорий Валериевич кандидат медицинских наук, доцент кафедры детской терапевтической стоматологии и профилактики стоматологических заболеваний Национального медицинского университета имени А. А. Богомольца. 03680, г. Киев, ул. Зоологическая, 1, каб. 325, тел. +380667226456 Е-mail - sorochenkogw@mail.ru Grigoriy Sorochenko Ph.D in dentistry Professor assistant, department of pediatric and preventative dentistry Bogomolets national medical university 1, Zoologichna str., Kyiv, 03680, tel. +380667226456 Резюме. Методом сканирующей электронной микроскопии изучены in vitro морфологические изменения поверхностного слоя 35 образцов эмали постоянных зубов, которые только что прорезались, под воздействием водорастворимого крема, который содержит казеинфосфопептид-аморфный фосфат кальция и зубной пасты, которая содержит 5000 ррм фтора. Установлено, что эмаль зубов, которые только что прорезались, имеет визуальные признаки недостаточной минерализации и, соответственно, имеет недостаточный уровень кариесрезистентности; в течение эксперимента под воздействием исследуемых средств экзогенной профилактики на поверхности эмали наблюдаются морфологические изменения, которые свидетельствуют об увеличении степени минерализации. Ключевые слова: эмаль, постоянные зубы, минерализация, казеинфосфопептид-аморфный фосфат кальция, зубные пасты, фтор, профилактика кариеса. Summary. Using scanning electrone microscopy we studied in vitro morphological changes of the superficial layer of 35 just erupted permanent teeth enamel samples under the influence of a water-soluble cream containing casein phosphopeptide – amorphous calcium phosphate and a toothpaste with 5000 ppm of fluoride ions. We found that the enamel of just erupted teeth has visual signs of insufficient mineralization and, therefore, has insufficient level of caries resistance; during the experiment we observed morphological changes of enamel surfaces that indicate an increase in the degree of mineralization under the influence of investigated agents for exogenous prevention. Key words: enamel, permanent teeth, mineralization, casein phosphopeptide - amorphous calcium phosphate, fluoride, toothpastes, caries prevention.